2023
DOI: 10.1002/cam4.6279
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging findings of intracranial extraventricular ependymoma: A retrospective multi‐center cohort study of 114 cases

Liyan Li,
Yan Fu,
Yinping Zhang
et al.

Abstract: BackgroundIntracranial extraventricular ependymoma (IEE) is an ependymoma located in the brain parenchyma outside the ventricles. IEE has overlapping clinical and imaging characteristics with glioblastoma multiforme (GBM) but different treatment strategy and prognosis. Therefore, an accurate preoperative diagnosis is necessary for optimizing therapy for IEE.MethodsA retrospective multicenter cohort of IEE and GBM was identified. MR imaging characteristics assessed with the Visually Accessible Rembrandt Images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The clinical variables such as serum creatinine and eosinophils were included in the analysis of this cohort because prior studies have indicated the relevance of these variables for survival and prognosis in patients with GBM ( 23 , 24 ). We have previously published a study on the same cohort focusing on MRI imaging findings of IEE and GBM ( 25 ). The present study extended our research beyond imaging characteristics and tested a machine learning algorithm for differentiating IEE from GBM.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical variables such as serum creatinine and eosinophils were included in the analysis of this cohort because prior studies have indicated the relevance of these variables for survival and prognosis in patients with GBM ( 23 , 24 ). We have previously published a study on the same cohort focusing on MRI imaging findings of IEE and GBM ( 25 ). The present study extended our research beyond imaging characteristics and tested a machine learning algorithm for differentiating IEE from GBM.…”
Section: Methodsmentioning
confidence: 99%